Influence of metabolic syndrome on post-stroke outcome, angiogenesis and vascular function in old rats determined by dynamic contrast enhanced MRI. Issue 7 (July 2021) - Pradillo, Jesús M; Hernández-Jiménez, Macarena; Fernández-Valle, María E; Medina, Violeta; Ortuño, Juan E; Allan, Stuart M; Proctor, Spencer D; Garcia-Segura, Juan M; Ledesma-Carbayo, María J; Santos, Andrés; Moro, María A; Lizasoain, Ignacio
Stroke affects primarily aged and co-morbid people, aspects not properly considered to date. Since angiogenesis/vasculogenesis are key processes for stroke recovery, we purposed to determine how different co-morbidities affect the outcome and angiogenesis/vasculogenesis, using a rodent model of metabolic syndrome, and by dynamic enhanced-contrast imaging (DCE-MRI) to assess its non-invasive potential to determine these processes. Twenty/twenty-two month-old corpulent (JCR:LA-Cp/Cp), a model of metabolic syndrome and lean rats were used. After inducing the experimental ischemia by transient MCAO, angiogenesis was analyzed by histology, vasculogenesis by determination of endothelial progenitor cells in peripheral blood by flow cytometry and evaluating their pro-angiogenic properties in culture and the vascular function by DCE-MRI at 3, 7 and 28 days after tMCAO. Our results show an increased infarct volume, BBB damage and an impaired outcome in corpulent rats compared with their lean counterparts. Corpulent rats also displayed worse post-stroke angiogenesis/vasculogenesis, outcome that translated in an impaired vascular function determined by DCE-MRI. These data confirm that outcome and angiogenesis/vasculogenesis induced by stroke in old rats are negatively affected by the co-morbidities present in the corpulent genotype and also that DCE-MRI might be a technique useful for the non-invasive evaluation of vascular function and angiogenesis processes.